How The Prepositional Phrase Arouses Ambiguity In Three Articles Published On Search.Ebscohost.com - Dede ismail (English Journal Literacy Utama, 2022)
This research is entitled How the Prepositional Phrase Arouses Ambiguity in Three Articles Published on Search.ebschost.com. The purpose of this research is to discuss some sentences containing prepositional phrase which enables the author to find its ambiguity and its solution. This prepositional phrase analysis is done by studying some previous articles found in Search.ebschost.com. The preposition phrase chosen to be analyzed refers to the preposition phrase which begins with the preposition “with”. The result that can be taken from this research shows that (1) the prepositional phrase may attach only to VP in particular sentence, while on the other hand, (2) it may attach both to VP and to NP so that the meaning of the sentence may be ambiguous. To avoid the ambiguity, the possessive determiners and the relative clauses may be used instead. The qualitative method was employed since it referred to the theoretical frames which consists of previous researches, findings, and theories.